Determinants of Personal Protective Equipment (PPE) Compliance Among Workers - La Ode Asrianto; Amrun; Teti Susliyanti (PT. Nasyah Medika Care, 2024)
Background: Personal Protective Equipment (PPE) is an essential component of occupational safety and health, serving as the last line of defense against workplace hazards. Despite the availability of PPE in many workplaces, worker compliance remains suboptimal, contributing to occupational injuries and reduced productivity. Understanding the determinants of PPE compliance is essential for developing effective workplace safety interventions, particularly in rapidly developing regions such as Baubau City, Southeast Sulawesi. Research Objective: This study aimed to identify the determinants of Personal Protective Equipment (PPE) compliance among workers in Baubau City, Southeast Sulawesi. Methods: An analytical cross-sectional study was conducted from May to July 2026 involving 120 workers selected through proportionate random sampling. Data were collected using a structured questionnaire assessing respondents' characteristics, knowledge, attitudes, occupational safety training, supervision, PPE availability, management support, and PPE compliance. Data were analyzed using descriptive statistics, the Chi-square test for bivariate analysis, and multiple logistic regression to determine the dominant factors associated with PPE compliance. Statistical significance was established at p < 0.05. Results: The majority of respondents (69.2%) were compliant with PPE use. Bivariate analysis revealed significant associations between PPE compliance and knowledge (p = 0.001), attitude (p = 0.002), occupational safety training (p = 0.004), supervision (p = 0.001), PPE availability (p = 0.006), and management support (p = 0.001). Multiple logistic regression identified supervision as the strongest determinant of PPE compliance (AOR = 3.41; 95% CI: 1.52–7.67; p = 0.003). Conclusion: PPE compliance among workers is influenced by both individual and organizational factors, with supervision emerging as the strongest predictor. Strengthening occupational safety training, ensuring adequate PPE availability, enhancing workplace supervision, and reinforcing management commitment are recommended to improve PPE compliance and reduce occupational injuries.